2018
DOI: 10.3126/jmmihs.v4i1.21132
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and hematological parameters in chronic kidney disease

Abstract: Background: Chronic kidney disease is a worldwide public health problem. It is associated with various biochemical and hematological abnormalities that leads to morbidity and mortality. The aim of this study was to evaluate the biochemical and hematological parameters in chronic kidney disease patients.Methods: This is a prospective cross sectional study conducted over a period of six months on 52 chronic kidney disease patients at Kist Medical College Teaching Hospital, Lalitpur, Nepal. Biochemical parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 6 publications
6
8
0
Order By: Relevance
“…Elevated creatinine and urea levels are likely evidence of decreased kidney function (5) . Bagalad et al (17) ,de Almeida et al (18) , Dash et al (19) and several studies done earlier also in agreement with our results and found that urea and creatinine were highly elevated in CKD patients prior dialysis and eventually decreased due to hemodialysis and there was a significant fall in serum creatinine level after hemodialysis as compared with pre-dialysis patients (20) . During hemodialysis, excess urea from the patient's blood is slightly removed in order to prevent accumulation.…”
Section: Figure 6: Correlation Between Fetuin-a and S Creatinine In Ckd Patients After Dialysissupporting
confidence: 93%
“…Elevated creatinine and urea levels are likely evidence of decreased kidney function (5) . Bagalad et al (17) ,de Almeida et al (18) , Dash et al (19) and several studies done earlier also in agreement with our results and found that urea and creatinine were highly elevated in CKD patients prior dialysis and eventually decreased due to hemodialysis and there was a significant fall in serum creatinine level after hemodialysis as compared with pre-dialysis patients (20) . During hemodialysis, excess urea from the patient's blood is slightly removed in order to prevent accumulation.…”
Section: Figure 6: Correlation Between Fetuin-a and S Creatinine In Ckd Patients After Dialysissupporting
confidence: 93%
“…These values are lower than the control group, which is statistically significant change (p<0.5). Similar result are mentioned in other studies in chronic kidney disease patients, as mentioned from Singh et. al., 2018, Habib et al 2017, Suresh et al 2012, Yassein et al 2016and Alghythan et al, 2013.…”
Section: Figure 2 Etiology Of Chronic Kidney Diseasesupporting
confidence: 92%
“…It is noticed that males are more affected by chronic kidney disease and maintained on dialysis when compared to females as shown in table 1. Similar data are presented in other studies of the same profile, showing a predominance of male compared to female as mentioned bySingh et al 2018and Islam et al 2015and by Ansari et al 2021. From the data distribution we can see that the more problematic age is from 50 to 69 years old as shown in table1 and figure 1.…”
supporting
confidence: 90%
“…The reduction in the synthesis of erythropoietin related to renal failure is the main reason for this abnormality. Other factors such as increased hemolysis, inflammation, chronic blood loss, nutritional deficiency, hyperparathyroidism, and marrow suppression can also contribute to the disease severity [ 14 ].…”
Section: Discussionmentioning
confidence: 99%